1992
DOI: 10.1002/ar.1092330417
|View full text |Cite
|
Sign up to set email alerts
|

Stratificational relationship among the main nerves from the dorsal division of the sacral plexus and the innervation of the piriformis

Abstract: In order to comprehend more completely the morphology of the nerves to the piriformis, it is necessary to obtain a detailed understanding of the relationship of the origin and the course of these nerves from the dorsal division of the sacral plexus, with reference to the superior and inferior gluteal nerves. Twelve of seven human pelvic halves were carefully dissected in order to examine the origins of the nerves from the dorsal division of the sacral plexus. Six of these pelvic halves were further dissected u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 12 publications
(10 reference statements)
1
37
1
Order By: Relevance
“…Table shows the variations in the patterns of innervation of short lateral hip rotators as identified in anatomical textbooks, accompanied by analysis from cadaveric primary studies (Akita et al, ; Aung et al, ; Yadav et al, ) and review articles (Petchprapa et al, ; Petrie et al, ). In a detailed morphological investigation of the innervation of piriformis, Akita et al () observed multiple branches of the “nerves to the piriformis” in 12 Japanese cadavers, all arising from the nerves of posterior rami of the sacral plexus. From first six cadavers, Akita et al () noted branches arising from the caudal part of the superior gluteal nerve (6 of 6), the inferior gluteal nerve (3 of 6) and the common fibular nerve (1 of 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table shows the variations in the patterns of innervation of short lateral hip rotators as identified in anatomical textbooks, accompanied by analysis from cadaveric primary studies (Akita et al, ; Aung et al, ; Yadav et al, ) and review articles (Petchprapa et al, ; Petrie et al, ). In a detailed morphological investigation of the innervation of piriformis, Akita et al () observed multiple branches of the “nerves to the piriformis” in 12 Japanese cadavers, all arising from the nerves of posterior rami of the sacral plexus. From first six cadavers, Akita et al () noted branches arising from the caudal part of the superior gluteal nerve (6 of 6), the inferior gluteal nerve (3 of 6) and the common fibular nerve (1 of 6).…”
Section: Resultsmentioning
confidence: 99%
“…Akita et al (1994) used the former description in the 49 specimens they investigated, whereas in later studies, Nork et al (2005) (n 5 14) and Solomon et al (2010) (n 5 20) identified the piriformis origin using the latter terminology. In an earlier study, Akita et al (1992) described a variation in origin from "first to third pelvic sacral foramina" on one of the six specimens studied. Other textbooks McKinley and O'Loughlin, 2006) and an additional cadaveric study of four specimens (Snijders et al, 2006) describe the origin of piriformis from the anterolateral surface of the sacrum.…”
Section: Proximal Muscle Attachmentsmentioning
confidence: 99%
“…The origin of the superior gluteal nerve was found to be dorsal and more proximal to the origin of the inferior gluteal nerve (Akita et al, 1992). The origin of the superior gluteal nerve was found to be dorsal and more proximal to the origin of the inferior gluteal nerve (Akita et al, 1992).…”
Section: Superior Gluteal Nervementioning
confidence: 82%
“…Akita et al have studied the innervation of piriformis and glutei medius and minimus. [23][24][25] Based on the detailed findings of the innervation of the three muscles, they concluded that the muscle fibres of piriformis are chiefly composed of the caudal element of the gluteus medius muscle (89.8%) and in some cases the caudal element of the gluteus minimus muscle as well (10.2%). 24 The peroneal part of the sciatic nerve lies in the tissue plain superficial to gluteus minimus, and the tibial part of the sciatic nerve lies deep to this tissue plain, so when a portion of piriformis is formed by the gluteus minimus muscle layer, it divides the sciatic nerve.…”
Section: Aetiologymentioning
confidence: 99%